Effect of microwave-assisted treatment on the composition of spray-dried Porphyridium cruentum extract (One Health & Risk Management, 2025)
Introduction: Microalgae represents a valuable source of natural products with bioactive properties, having applications in biomedicine, the pharmaceutical industry, nutrition, and cosmetics. The red microalga Porphyridium cruentum stands out for its rich content of biomolecules with antioxidant, anti-inflammatory, and immunomodulatory effects. Applying efficient extraction and preservation methods is essential to optimize the utilization of these biomolecules.Materials and Methods: The biomass of Porphyridium cruentum was treated with microwaves at 180W, 300W, and 450W for 10, 20, and 30 seconds, followed by aqueous extraction at 80°C. The powders were obtained by spray drying at 100°C. The aqueous extracts and the obtained powders were evaluated for their composition (proteins, carbohydrates, phenolic compounds) and antioxidant activity (ABTS and DPPH assays).Results: Moderate microwave treatment (180W for 20–30 seconds) enhanced the extraction of proteins and carbohydrates while maintaining high antioxidant activity. The obtained powders retained up to 90.96% of proteins, 95.81% of carbohydrates, and 74.91% of phenolic compounds, with minimal antioxidant activity losses after six months of storage.Conclusions: This study's results demonstrate that treating Porphyridium cruentum biomass with microwaves, followed by aqueous extraction and spray drying extract, represents an effective strategy for obtaining and preserving microalgal bioactive compounds. This approach facilitates their application in the pharmaceutical, nutraceutical, and cosmetic fields.